2015
DOI: 10.1021/jp511120j
|View full text |Cite
|
Sign up to set email alerts
|

Charge Redistribution Effects on the UV–Vis Spectra of Small Ligated Gold Clusters: a Computational Study

Abstract: We analyze and compare the UV-Visible absorption profiles, computed at the TD-DFT level, of several thiolate, chloride and phosphine ligand protected gold clusters with Au 13 , Au 25 and Au 28 metallic cores. We show by investigating several model clusters and experimentally reported ones that the charge redistribution between the gold core and the ligand shell can be controlled by the electron acceptor or electron donor character of the ligands and their spatial distribution around the metallic core. A correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…However, the charge on these clusters, Au 25 (SR) 18 and Ag 25 (SR) 18 , is not localized but dispersed over atoms in their core, staples and ligands2329. Hence, the two clusters may not experience considerable repulsive interactions between them when they approach each other.…”
Section: Resultsmentioning
confidence: 99%
“…However, the charge on these clusters, Au 25 (SR) 18 and Ag 25 (SR) 18 , is not localized but dispersed over atoms in their core, staples and ligands2329. Hence, the two clusters may not experience considerable repulsive interactions between them when they approach each other.…”
Section: Resultsmentioning
confidence: 99%
“…[17] However,t he need for atomically precise syntheses or separation methods limits the surface chemistries that can be explored, and experimental methods sensitive to electronic structure typically do not provide the necessary detail to identify trends or benchmark quantum chemical studies. [14,18,19] Thec ombination of anisotropic solvent environments,t hermal averaging, impurities,a nd ligand dissociation or core isomerization obfuscate quantitative comparisons between species or with quantum chemical predictions,h ampering efforts to develop ac ohesive framework to rationalize electronic structure and necessitating anew approach. [8,14,[20][21][22] In order to overcome such challenges,w et urned to cryogenic ion trap photofragmentation spectroscopy,ameasurement which combines the selectivity of mass-spectrometry with the spectral detail of low-temperature UV/Vis spectroscopy to provide ap robe of electronic structure approaching the physical limit of spectroscopic resolving power.…”
Section: Systematically Tuning the Electronic Structure Of Gold Nanocmentioning
confidence: 99%
“…Pohjolainen et al found that changing the ligand anchor atom had a pronounced effect on optical spectra . Lugo et al found by changing the chemistry of the ligand on different sized AuNCs that the more negative the partial charge on the core, the more the lowest absorption band was shifted to the red …”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…[ 74 ] Lugo et al found by changing the chemistry of the ligand on different sized AuNCs that the more negative the partial charge on the core, the more the lowest absorption band was shifted to the red. [ 75 ] While TDDFT is an exceptional method for examining the optical properties of NPs, it is not the only useful technique to do so. Tlahuice-Flores et al found that far-IR and low-frequency Raman can be used to fi ngerprint AuNCs using standard DFT methods for calculating IR spectra.…”
Section: Optical and Electronic Propertiesmentioning
confidence: 99%